Effects of polyploidization on the contents of photosynthetic pigments are largely population-specific - Münzbergová, Zuzana; Haisel, Daniel (Photosynthesis research, 2019)
The contents of photosynthetic pigments are an important indicator of many processes taking place in the plant body. Still, however, our knowledge of the effects of polyploidization, a major driver of speciation in vascular plants, on the contents of photosynthetic pigments is very sparse. We compared the contents of photosynthetic pigments among natural diploids, natural tetraploids, and synthetic tetraploids. The material originated from four natural mixed-cytotype populations of diploid and autotetraploid Vicia cracca (Fabaceae) occurring in the contact zone between the cytotypes in Central Europe and was cultivated under uniform conditions. We explored whether the contents of pigments are primarily driven by polyploidization or by subsequent evolution of the polyploid lineage and whether the patterns differ between populations. We also explored the relationship between pigment contents and plant performance. We found very few significant effects of the cytotype on the individual pigments but many significant interactions between the cytotype and the population. In pair-wise comparisons, many comparisons were not significant. The prevailing pattern among the significant once was that the contents of pigments were determined by polyploidization rather than by subsequent evolution of the polyploid lineage. The contents of the pigments turned out to be a useful predictor of plant performance not only at the time of material collection, but also at the end of the growing season. Further studies exploring differences in the contents of photosynthetic pigments in different cytotypes using replicated populations and assessing their relationship to plant performance are needed to assess the generality of our findings.
Keywords: Photosynthesis; vikev; biologické pigmenty; Carotenoids; Vicia; Legume; Photoprotective pigments; Plant performance; Pigments, Biological; fotosyntéza; polyploidie; Polyploidy; Diploidy; tetraploidie; Tetraploidy; Colchicine; Synthetic polyploids; diploidie